2010
DOI: 10.1557/jmr.2010.0019
|View full text |Cite
|
Sign up to set email alerts
|

Improved current collection in WO3:Mo/WO3 bilayer photoelectrodes

Abstract: We report on the incorporation of molybdenum into tungsten oxide by co-sputtering and its effect on solar-powered photoelectrochemical (PEC) water splitting. Our study shows that Mo incorporation in the bulk of the film (WO 3 :Mo) results in poor PEC performance when compared with pure WO 3 , most likely due to defects that trap photo-generated charge carriers. However, when a WO 3 :Mo/WO 3 bilayer electrode is used, a 20% increase of the photocurrent density at 1.6 V versus saturated calomel reference electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 20 publications
(11 reference statements)
1
27
0
Order By: Relevance
“…We have substituted WO 3 to 5% with various cations (including 5% Mo) and found in no single case an increased photocurrent [27]. Interestingly, if the tungsten oxide is not bulk doped, but coated with a thin Mo-oxide film on top of the WO 3 , then an increased photocurrent was measured [28]. According to the authors, coherent growth of the Mo oxide on the WO 3 allows optimization of the electronic surface structure of the electrode while maintaining good crystallographic properties in the bulk.…”
Section: Surface and Sub-surface Studies On Tungsten And Iron Oxide Pmentioning
confidence: 98%
“…We have substituted WO 3 to 5% with various cations (including 5% Mo) and found in no single case an increased photocurrent [27]. Interestingly, if the tungsten oxide is not bulk doped, but coated with a thin Mo-oxide film on top of the WO 3 , then an increased photocurrent was measured [28]. According to the authors, coherent growth of the Mo oxide on the WO 3 allows optimization of the electronic surface structure of the electrode while maintaining good crystallographic properties in the bulk.…”
Section: Surface and Sub-surface Studies On Tungsten And Iron Oxide Pmentioning
confidence: 98%
“…7 Contrary to other reports, 8 resulting WO 3 : Mo photoanodes produced less photocurrent than pure ͑Mo-free͒ WO 3 electrodes. 7 We found that the Mo incorporation had no pronounced impact on the band gap but negatively affected the ͑micro͒structural properties of the photoanode material. 7 To circumvent the latter, we introduced a WO 3 :Mo/ WO 3 bilayer electrode, which showed a ϳ20% photocurrent improvement compared to WO 3 single layers.…”
mentioning
confidence: 68%
“…To tailor the optical properties of the WO 3 photoanode, we have thus incorporated Mo. 7 Contrary to other reports, 8 resulting WO 3 : Mo photoanodes produced less photocurrent than pure ͑Mo-free͒ WO 3 electrodes. 7 We found that the Mo incorporation had no pronounced impact on the band gap but negatively affected the ͑micro͒structural properties of the photoanode material.…”
mentioning
confidence: 99%
“…However, the WO 3 :Mo/WO 3 homojunction with a good interface and type II band alignment provided a 20% increase of the photocurrent density at 1.6 V vs. SCE (saturated calomel reference electrode) as opposed to pure WO 3 , because a built-in potential was created at the WO 3 :Mo/WO 3 homojunction, as illustrated in Fig. 5 [52,53]. Building internal fields through the introduction of p/nand homo-junctions buried in a semiconductor through doping control is a classic approach for the construction of electronic devices and solar cells.…”
Section: Nanojunctionmentioning
confidence: 99%
“…(b) Band alignment of WO 3 :Mo/WO 3 homojunctions. (c) Photocurrent density of WO 3 , WO 3 :Mo, WO 3 :Mo/WO 3 under illumination[52,53].…”
mentioning
confidence: 99%